Who Are You and Who Are We? Gaze and Identity in Bling Empire - So Young Koo (Global Storytelling)
The twenty-first century saw a rise in popularity and interest in East Asian cultural and media products. First created for the local audience, they are now disseminated globally, carrying with them the cultural and identity conflicts of their respective societies. Netflix’s Bling Empire makes a similar journey as the first US reality TV series with an all-Asian main cast. The cast is mostly East Asian whose narrative centers on the ideas of movement and diaspora reflecting the journey of cultures and ideas across national borders. While this journey allows for an increased understanding of cross-cultural influences, cultural nuances are often lost. Bling Empire foregrounds exaggerated caricatures of Asian Americanness and instead globally circulates surface-y stereotypes. The inability to fully grasp the cultural insight necessary to understand these cultural and media products is a further commentary on the danger of “glocal” products of the twenty-first century. Netflix’s Bling Empire embodies seemingly contrasting American and Asian experiences in the United States. Inspired by Laura Mulvey’s theory of the male gaze, this essay attempts to analyze how the gaze functions in the identity-making of the cast members as they interact in the construction and reception of the series. While unified in their expression of material wealth, the cast members range from immigrant to Asian American to adoptee experiences. The varying backgrounds of the cast members reflect existing structures of real-world cultural interactions. The series weaves very personal struggles of marriage, family, infertility, and relationships to the heightened awareness of the gaze cues. Therefore, the gaze helps to explain the internalized external gaze cues the cast members, and by extension the audience, must negotiate in the understanding of their constructed world.